Pengaruh Penggunaan Catalytic Converter Kuningan (Cu+Zn) Berlapis Krom (Cr) Terhadap Torsi Dan Daya Efektif Motor Bensin Empat Langkah - Warju, (Teknika, 2007)
The use of catalytic converter that placed on vehicle exhaust system can decrease exhaust gas emission consentration from four stroke gasoline engine. From previous research with using chrom (Cr) coated brass (Cu+Zn) as catalytic converter can reduce CO, HC and NOx emission. But, the use of catalytic converter on vehicle exhaust system also influent engine performance. Purpose of this research is to know influent of the use catalytic converter on Toyota Kijang Type 4K exhaust system to torque and engine power.The experiment was carried out at Automotive Laboratory PPPGT/VEDC Malang. In this experiment Toyota Kijang Type 4K series KF20 engine was used. The test method is done by velocity gradient at full load (full open trottle valve). The test was carried out by comparing standard engine experiment and engine experiment with catalytic converter on exhaust system. The type of the test is desk test. Data analysis is done by using descriptive methods. The analysis shows that chrom (Cr) coated brass (Cu+Zn) as catalytic converter increase engine torque is up to 2,34% at 1750 rpm and lower engine torque increase is up to 0,09% at 2750 rpm. The greatest engine power increase is up to 2,35% at 1750 rpm and lower engine power increase is up to 0,09% at 2750 rpm.